O conceito de felicidade na filosifia prática de Kant - Difante, Édison Martinho da Silva (2008)
This dissertation aims to present a reconstruction of the concept of happiness in the practical philosophy of Kant. This theme is not restricted to only one work in Kant, rather it appears in several: in The Critique of Practical Reason (CRPr), in The Groundwork of Metaphysics of Morals (FMC), in The Metaphysics of Morals (MC), in The Anthropology from a Pragmatic Point of View (A), and, inclusively, in The Critique of Pure Reason (CRP). The first section of the dissertation gives a brief exposition of the moral rule and the practical principles of acting, in an attempt to elucidate the concept of autonomy of will, which is fundamental for the justification of morality, and without which man could not be thought of as an end in himself. This is followed by an elaboration on the conception of happiness as empiric satisfaction, which tends to justify, on the one hand, why Kant excludes it in that which concerns the justification of moral acting; and on the other hand, why its presence or absence can assist or hinder the achievement of moral duty. Subsequently, from a criticalsystematic perspective, and based on the analysis of the concept of summum bonum, considered to be the a priori object of morality, an effort is made to show the systematic function of happiness in the context of practical Kantian philosophy. At this point, the issue that surfaces is: though happiness cannot exert any role in that which concerns moral justification, it, nevertheless, becomes an element of extreme importance in the effectuation or possible realization of morality. From there, why Kant does not exclude it definitively, although he does not give it the same focus that the philosophical tradition had given it until then. When one thinks of the perfect good for a rational being, happiness should be included as well, but under the condition of worthiness. Happiness, from this point of view, no longer consists of the satisfaction of necessities, tendencies and human impulses, but is merely a concept of the moral world.